Kajian Etis Normatif dalam Pendidikan Arsitektur di Era Industri 4.0 - Johannes Adiyanto (ARSITEKTURA, 2019)
Industry 4.0 is a necessity in the current global era. Indonesia since 2018 has prepared itself with the "Making Indonesia 4.0" roadmap, which covers the food and beverage, textile, automotive, electronics and chemical industries. This program is also supported by a link and match program between the Ministry of Industry and the Ministry of Research, Technology and Higher Education. On the other hand, the development of the use of BIM and 3D printers in building construction has begun to develop rapidly. The construction approach 4.0 will soon be entering Indonesia so, that the link and match with the world of education need to be a concern. Is it the education of architecture in Indonesia already prepare for that technology? That is the main question in this paper. This research approach is a normative ethical philosophy approach. The method used is a normative qualitative method and makes a comparison between the phenomena of industrial development 4.0, especially those related to construction 4.0 with the latest developments in the world of education, especially architectural education in Indonesia. This comparison is then compared with legislation related to undergraduate higher education in the department / architecture study program. These appeals become the basis for the stages of discussion that see developments into the future of the IT world related to architecture. This research shows that there is something fundamental in the present development, namely the aspect of cooperation. The aspect of cooperation is the key to the use of BIM, and this is also the main variable in legislation which is termed the humanities value. Thus the difficulty of using BIM software in various universities due to various technical and non-technical reasons is not an obstacle to pursuing standards that are consistent with the development of the phenomenon of the Industrial Revolution 4.0. This can be said because the development of BIM in the future is not only talking about technical matters, but also on social problems, especially human capabilities collaboratively. The ability of collaboration between designers and the ability of collaboration across sciences is an important capability in the future.